A centralidade da estrutura psíquica e sua função na reformulação da experiência interna na psicologia descritiva e analítica: considerações sobre o princípio de fenomenalidade na psicologia de Dilthey - Matteucci, Antonio Batista (2021)
Our efforts were focused on addressing the presentation of Dilthey's psychology, mainly on the concept of internal experience as a structured psychic system. We are not innovating here: our work only collects and compiles theses already defended and widely followed among the most important scholars of Dilthey's work. As for the path we have taken in the present work, we follow the theses mainly of Makkreel in Dilthey: philosopher of the human studies (1975) and of Hodges in The Philosophy of Wilhelm Dilthey (1952). Our work will try to present the most important points of Dilthey's descriptive psychology, but, touching on the points of intersection of the different themes in which we see as fundamental the notion of internal experience as a psychic nexus or psychic structure